Aprendizagem reflexiva de enfermeiras na atenção domiciliar: caminhos para uma práxis criadora - Angélica Mônica Andrade (2017)
The execution of this study started from the premise that there are estrangements between the academic training of nurses and the processes required for working in home care. As a consequence, the invisibility of home care in the training of nurses highlights the need for learning in its work context, thereby generating implications in its praxis. The thesis was built on the basis of the theoretical categories:Reflective learning and Praxis, according to the frameworks of Donald Schön and Adolfo Sánchez Vázquez, respectively. This study was intended to analyze the learning process and the praxis of the nursein home care. We performed a unique Case Study, with a qualitative nature, which was anchored in the theoretical-methodological framework of dialectics. The production of datatook place in home care services of the Unified Health System in the cities of Uberlândia and Betim, in Minas Gerais, and happened in two moments: participant observation of the work of thirteen nurses and accomplishment of interviews. The data were submitted to Critical Discourse Analysis, under the Faircloughs perspective, which enabled the discussion of three empirical categories: Practice of the nurse at home: actions and knowledge mobilized by reflexivity; Reflective learning: situations, sources and mediators; and Praxis in the work of the nurse at home. The results signalized the presence of actions and skills mobilized by the reflective practice of the nurse at home in a continuous and cyclical movement of learning evidenced by the discursive practices. The praxis in the work of the nurse at home is revealed in a dialectical relationship of interdependence between theory and practice,which is builtby means ofadaptations and (re) inventions, where learning was evidenced in situations that arouse reflexivity, through practice, experience and experimentation. The discourses point out ways of reaching a path to the creative praxis of the nurse at home, since work is marked by unrepeatability and unpredictability. Accordingly, there are forces that modify the established plan, thereby requiring the constant and active presence of consciousness and the capacity for creation. At other moments, the reiteration of praxis was evidenced, although self-consciousness was manifested and triggered by the need for solutions to the problems faced in home care. We can conclude that the practice of nurses in home care is established in the combination of a reiterative, spontaneous, reflective and creative praxis,throughthe action and reflection arising from the knowledge gathered throughout the academic training, which is redefined in the face of the reality experienced in the daily life at home in a process of reflective learning.